Gandhi and the Stoics modern experiments on ancient values - Sorabji, Richard (Oxford : Oxford University Press, 2012)
Richard Sorabji presents a study of Gandhi's philosophy in comparison with Christian and Stoic thought. He shows that Gandhi was a true philosopher, who not only aimed to give a consistent self-critical rationale for his views, but also thought himself obliged to live by what he taught.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Philosophy; Philosophy, Indic; Stoics; Christian philosophy